The Analysis of the Implementation Factors of the Platform Merdeka Mengajar (PMM) Using the Human Organization Technology (Hot) Fit Models - Heni Triastuti; Priyanto (Department of Electronic and Informatic Engineering Education, Faculty of Engineering, UNY, 2025)
Platform Merdeka Mengajar (PMM) has not been utilized optimally as a medium for learning, sharing, innovating and inspiring. There are still cases of teachers who have not completed training and real action on the independent teaching platform. This research aims to obtain the highest and lowest values for factors inhibiting the success of implementing the Merdeka Mengajar Platform (PMM) in Sleman Regency based on the HOT Fit Models. The research used the Human Organization Technology Fit Model approach. The research was conducted using a sample of 100 teachers consisting of 6 kindergarten teachers, 6 elementary school teachers, and 88 junior high school teachers who are under the auspices of the Sleman Regency Education Office. In this study, data analysis was carried out using SmartPLS software version 3.2.9. The results of the research explained that system quality (t count 0.598 < t table 2.23) did not have a significant impact on system use; system quality (t count 1.197 < t table 2.23) does not have a significant impact on user satisfaction; information quality (t count 1.146 < t table 2.23) does not have a significant impact on system use; information quality (t count 5.057 > t table 2.23) has a significant impact on user satisfaction; service quality (t count 0.683 < t table 2.23) does not have a significant impact on system use; service quality (t count 0.251 < t table 2.23) has no significant impact on user satisfaction; user satisfaction (t count 3.434 > t table 2.23) has a significant impact on system use; user satisfaction (t count 2.993 > t table 2.23) has a significant impact on net benefit; system use (t count 1.557 < t table 2.23) does not have a significant impact on net benefit; organizational structure (t count 13.422 > t table 2.23) has a significant impact on the organizational environment; organizational structure (t count 0.564 < t table 2.23) does not have a significant impact on net benefits; organizational environment (t count 2.291 > t table 2.23) has a significant impact on net benefits. Based on these results, it can be concluded that the highest value that influences the implementation of the independent teaching platform is organizational structure on the organizational environment, while the lowest value is service quality on user satisfaction, respectively, with a t-count of 13.422 and 0.251.